Impact of prenatal tobacco smoking on infant telomere length trajectory and ADHD symptoms at 18 months: a longitudinal cohort study - Meghan P. Howell (BMC Medicine, 2022)
Abstract Background Prenatal maternal tobacco smoking is a predictor of child attention-deficit/hyperactivity disorder (ADHD) and is associated with offspring telomere length (TL). In this study, we examine the relationship between maternal prenatal smoking, infant TL, and maternal report of early childhood symptoms of ADHD. Methods One-hundred and eighty-one mother-infant dyads were followed prospectively for the infant’s first 18 months of life. Prenatal smoking was assessed from maternal report and medical records. TL was measured from infant buccal swab DNA obtained across the first 18 months of life. ADHD symptoms were obtained from maternal report on the Child Behavior Check List. Multiple regression models tested the relation between prenatal smoking and both ADHD symptoms and infant TL. Additional analyses tested whether the change in infant TL influenced the relation between prenatal smoking and ADHD symptoms. Results Sixteen percent of mothers reported prenatal smoking. Infant TL at 4, 12, and 18 months of age were correlated. Consistent with previous cross-sectional studies linking shorter offspring TL to maternal prenatal smoking, maternal prenatal smoking predicted greater telomere shortening from four to 18 months of infant age (β = − 5.797, 95% CI [-10.207, -1.386]; p = 0.010). Maternal depression was positively associated with both prenatal smoking (odds ratio (OR): 4.614, 95% CI [1.733, 12.282]; p = 0.002) and child ADHD symptoms (β = 4.713, 95% CI [2.073, 7.354]; p = 0.0006). To prevent confounding, analyses examined the relation between TL, ADHD symptoms, and prenatal smoking only in non-depressed mothers. In non-depressed mothers, infant TL attrition across the first 18 months moderated the relation between smoking and child ADHD. Conclusions The findings extend previous studies linking prenatal smoking to shorter infant TL by providing data demonstrating the effect on TL trajectory. The relation between prenatal smoking and early infant ADHD symptoms was moderated by the change in TL. The findings provide novel initial evidence suggesting that TL dynamics are one mechanistic pathway influencing the relation between maternal prenatal smoking and ADHD.